Unveiling the Influence of Technology Anxiety on Facial Recognition Payment: Does the Golden Age Citizen Adopt the Payment with their Face? - Zhou, Yuhan; Bohari, Abdul Manaf (International Review of Management and Marketing, 2026)
This study examines the moderating role of technology anxiety (TA) in the relationship between trust, satisfaction, and the intention to use facial recognition payment (FRP), focusing on the senior citizens in Tangshan City, China. With the latest development of China’s cashless society, FRP has been widely adopted among young generation due to its convenience and security. However, senior citizen users face significant psychological barriers due to technology anxiety as mentioned by many studies. The research integrates the framework of Belief-Attitude-Intention (B-A-I) framework and the Technology-Organization-Environment-Individual (TOE-I) to propose a theoretical model and develop research hypotheses, with a focus on analysing how technology anxiety moderates the relationship between attitudes and behavioural intentions, specifically on senior citizen users. At the theoretical level, this study expands the theoretical perspective of biometric payment system adoption research by introducing technology anxiety as a moderating variable. At the practical level, the findings provide reference for policymakers and businesses to design elderly-friendly digital payment solutions, suggesting targeted interventions (e.g., digital literacy training) to reduce technology anxiety and promote the adoption of emerging payment technologies among the elderly. Suggestion will be made to improve the adoption level of FRP among the golden age citizen.